Determinants of Taxpayer Compliance on Property Tax: The Role of Tax Socialisation As A Moderating (Architecture Image Studies, 2025)
This study's objective is to offer empirical support that awareness, understanding, and income of taxpayers can increase compliance in paying property tax. In addition, there are differences in the effect of awareness, understanding, and income of taxpayers on compliance in paying property tax (PBB) between taxpayers who receive tax information and those who do not. The data collecting used a questionnaire survey, with 403 respondents. The study uses taxpayers who pay PBB in Jakarta, Indonesia as respondent. The sampling method used is convenience sampling. Data analysis method using moderating regression analysis. The result showed that taxpayer awareness has a positively impact on taxpayer compliance. Meanwhile, taxpayer understanding and income have no impact on taxpayer compliance. Tax socialisation effects on the relation between taxpayer awareness and understanding on tax compliance. Meanwhile, tax socialisation does not impact on the relation between taxpayer income and compliance. This research assists the government, particularly local governments, in identifying the causes of taxpayer non-compliance in paying local taxes, especially property tax, and provides recommendations for local governments to adopt policies to increase local revenue from the tax sector.